API Rate Limiting Mechanisms in SaaS Applications: A Systematic Analysis of DDoS Protection Strategies - Muthukrishnan Manoharan (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article comprehensively analyzes API rate-limiting mechanisms as a critical defense strategy against Distributed Denial-of-Service (DDoS) attacks in Software as a Service (SaaS) applications through systematic evaluation of three primary rate-limiting algorithms. The article examines Token Bucket, Leaky Bucket, and Sliding Window’s efficacy in protecting modern API infrastructures. The article synthesizes data from multiple case studies across diverse SaaS deployments, demonstrating a 94% reduction in successful DDoS attempts when implementing context-aware rate limiting compared to traditional IP-based approaches. The article particularly focuses on the performance implications of different rate-limiting strategies, revealing that sliding window implementations offer an optimal balance between security and legitimate request processing, with only a 2.3% false positive rate for high-traffic scenarios. Furthermore, the article proposes a novel framework for implementing adaptive rate limiting that dynamically adjusts thresholds based on historical traffic patterns and real-time threat analysis. The findings suggest that while all examined algorithms provide baseline protection, the implementation choice significantly impacts security efficacy and service availability. These insights contribute to the growing knowledge of API security and provide practical guidelines for implementing robust rate-limiting mechanisms in enterprise-scale SaaS environments.